AB1033 Challenges in Recruitment and Retention of Subjects in Conducting Clinical Drug Trials in A Developing Country. (15th July 2016) - Bhanushali, N.; Uppuluri, R.R.; Arava, S.; Younis, M.; Fatima, F.; Rani, A.; Kumar, D.; Jonnada, S.; Deepti, S.; Challa, S.; Challa, S.
Abstract : Background: Increasing enrollment and retention rates is important for clinical trials and healthcare advancements. Barriers in conducting clinical trials are physician-related, protocol-related or patient-related. Some of the factors that may hinder successful completion of a clinical drug trial are screen failures, adverse events leading to withdrawals and dropout of subjects. Inability to achieve adequate sample size for the trial may make the data insufficient to conclude objectives of a clinical drug trial and also increase overall cost and duration. Objectives: To study the factors such as subject recruitment and retention that may impede the successful conduct of clinical drug trials in India. Methods: Sixteen clinical drug trials conducted at a tertiary care for rheumatological disorders in Hyderabad, India were analyzed. The study period was during 2006–2015. Thirteen trials were pertained to rheumatoid arthritis (RA) and 3 to osteoarthritis (OA). Three trials were of phase II, 8 in phase III and 5 in phase IV. Ethics committee approval was obtained for each trial. After obtaining the informed consent, subjects were screened to evaluate study specific inclusion/exclusion criteria; those not fulfilling the criteria were not included into the trials. While conducting the trials the number of subjects withdrawn or dropped out was duly noted. Factors relating to subjects recruitment and retention were analyzed. Results: Among 228 screened subjects (mean age 47.3±11 years) women were 201 (88%). A total of 42 (18.4%) subjects were screen failed; 19 (45.3%) due to infection (latent tuberculosis) and 23 (54.7%) due to other reasons. One hundred and eighty six (81.6%) subjects were enrolled into the trials after fulfilling study specific inclusion and exclusion criteria. Screen failures were more in phase II (26.2%) and phase III (57.1%) trials; nearly half of them were due to latent tuberculosis. Among 186 subjects enrolled, 162 (87%) completed the trials and 24 (13%) discontinued. Half of the subjects discontinued (n=12) were withdrawn in view of adverse events. Two (8.3%) withdrew consent from the trials and 10 (41.7%) were lost to follow up. Maximum number of subjects discontinued was in phase IV (figure ). Conclusions: Screen failures have an impact on recruitment of the subjects. Number of screen failure was more in phase III. Number of screen failure was least and number of discontinuation was most in phase IV. In the present study nearly half of the subjects screen failed due to latent tuberculosis peculiar to endemic countries like India. Subject retention is also important in conducting successful clinical trials. In this study 40% of subjects dropped out due to unknown reasons. Further studies are required to analyze the factors related to subject recruitment and retention from the clinical trials conducted at other centers in developing countries like India. References: Peter Bower et al. Interventions to improve recruitment and retention in clinical trials: a survey and workshop to assess current practice and future priorities. Trials 2014; 15:399 Disclosure of Interest: None declared